Development of Arabic E-Book Media Based on Flip PDF Professional Application for Students - Morales, Utzinger; Joanan, Schittny; Julia, Hirsiger (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The learning process in which the atmosphere brings boredom and laziness and the lack of use of learning media is one of the factors in the lack of effective learning and the lack of enthusiasm of students in learning. For example, when learning takes place in schools, educators still use package books as materials in the learning process, so that educators cannot create a learning atmosphere. Therefore, educators need to increase their creativity by developing skills in making teaching materials in the form of utilizing technology-based learning media such as developing Arabic e-books using the Flip PDF Professional application. The purpose of this study was to develop Arabic e-books with the professional flip pdf application for junior high school students. In developing this e-book, researchers used the Research and Development (R&D) method with the Borg & Gall technique, the subjects in this study were 125 junior high school students. Based on large-scale testing, the results of the questionnaire of students' learning independence in the e-book developed reached an average percentage of 82%, namely the